Sharing without laws: an exploration of social practices and ad hoc labeling standards in online movie piracy - Roberto Tietzmann; Liana Gross Furini (Internet Policy Review, 2016)
This paper discusses self-labelling standards as sharing mediators in pirated versions of movies available online. Piracy has existed since the beginning of the film industry, challenging established rules and regulations. The dynamics of digital movie piracy often try to meet viewers' expectations while ignoring any regional and premiere date restrictions. Movie piracy organises its abundant offer by generating a self-regulatory repertoire of labeling standards. In this paper we propose an exploration of social practices related to the ad hoc labeling standards as regulators of a presumed user experience in unofficial versions of the movie Captain America: The Winter Soldier. Lessons for sharing economy regulation, especially in contexts where chaotic social relationships are involved, are identified and discussed.
Keywords: 300; Sharing economy; Piracy; Peer-to-peer (P2P)